Disposals of fixed property: timing of accrual and practical issues arising for provisional taxpayers - Barberton, Paul (Department of Finance and Tax, 2020)
When fixed property is disposed of the proceeds are generally received anywhere from three months to a year after the transaction is required to be recognised for income tax purposes. A provisional taxpayer could therefore be required to declare and pay tax prior to the receipt of these proceeds and therefore fund such tax from sources other than the transaction in question. The practical problem resulting from the time of accrual, and the due date of the tax payable in respect of such accrual, occurring prior to the receipt of the proceeds does not appear to have been addressed in the legislation. It is submitted that accrual date could be more closely linked to the date of transfer and receipt of the proceeds to mitigate this issue. The timing of such accruals is examined in the light of the conveyancing process, the relevant sections of the Income Tax Act, other taxes relevant in respect of disposals of fixed property, appropriate case law and accounting and SARS practices, in order to ascertain whether amendments to the Income Tax Act are justifiable. Particular attention is given to s 24(1) (“Credit agreements and debtors allowance”) following the ITC 14005 judgement which deemed the accrual to be the date of the agreement whether or not a credit agreement is extant. It is submitted that by making a few changes to the legislation, the risk of inequitable cash flow positions (and potential penalties) could be greatly reduced. While a closer alignment of tax accrual with cash receipt may have a material positive effect on taxpayers’ cash flows, the effect for SARS is arguably minimal.